John C. Calhoun papers - Calhoun, John C. (John Caldwell), 1782-1850.
Chiefly correspondence (1819-1849) of Calhoun with John R. Mathewes and Littleton Waller Tazewell; manuscript of Calhoun's last senate speech (1850 March 4) pertaining to the Compromise of 1850; list of rules (1828) for the U.S. commissioner of public buildings; and other papers.
A microfilm edition of the papers of John C. Calhoun in this and other collections in the Library of Congress Manuscript Division was made in 1957 by the National Archives under the auspices of the National Historical Publications Commission; cataloged in record 97-174701.
In part, photocopies and typewritten transcripts.
Reel guide for the microfilm edition available in the Library.
Vice president of the United States, U.S. secretary of state and secretary of war, and U.S. senator from South Carolina.
Collection material in English.
Keywords: Mathewes, John R. -- 1788-1867 -- Correspondence; Tazewell, Littleton Waller, -- 1774-1860 -- Correspondence; United States. -- Commissioner of Public Buildings; United States. -- Congress. -- Senate; Compromise of 1850.; South Carolina -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1815-1861.; Cabinet officers; Senators, U.S. Congress -- South Carolina; Vice-Presidents -- United States